1985
DOI: 10.4049/jimmunol.134.5.3032
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 suppresses human T helper/inducer lymphocyte activity in vitro.

Abstract: The active form of vitamin D3, 1 alpha,25-dihydroxyvitamin D3 (1,25-(OH)2-D3), suppresses in vitro immunoglobulin (Ig) production by activated peripheral blood mononuclear cells (PBM) from normal human subjects by inhibiting T helper/inducer TH cell activity. Normal PBM were fractionated into B, TH and T suppressor/cytotoxic (Ts) cells by fluorescence-activated cell sorting techniques. The resultant subsets were activated with mitogens and were cultured in the presence or absence of a receptor-saturating conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…36,37 Several studies have shown that vitamin D inhibits the synthesis and secretion of IL-2, IL-4, and IFN-γ and increases the expression of IL-5. [38][39][40][41][42][43][44] When compared to the results of our study on IL-2 and IL-4, the results are the opposite. Despite many controversies surrounding the effect of vitamin D on cytokine expression in patients with systemic lupus erythematosus, the results support the suggestion that reducing vitamin D3 deficiency is an effective way to control lupus.…”
Section: Discussionmentioning
confidence: 74%
“…36,37 Several studies have shown that vitamin D inhibits the synthesis and secretion of IL-2, IL-4, and IFN-γ and increases the expression of IL-5. [38][39][40][41][42][43][44] When compared to the results of our study on IL-2 and IL-4, the results are the opposite. Despite many controversies surrounding the effect of vitamin D on cytokine expression in patients with systemic lupus erythematosus, the results support the suggestion that reducing vitamin D3 deficiency is an effective way to control lupus.…”
Section: Discussionmentioning
confidence: 74%
“…59,61 Although the underlying mechanisms of vitamin D's protection against severe COVID-19 are unknown, it is established that vitamin D reduces the production of proinflammatory cytokines such as Th1, TNF-α, interferon-β, IL-6, and promotes the production of anti-inflammatory responses such as T regulatory cells and Th2. 49,59,[62][63][64] There are several explanations for vitamin D's beneficial effects on critically ill patients. Initially, critically ill patients who are given vitamin D supplements will have their plasma vitamin D concentrations restored.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive effect of VD 3 is correlated with a decrease in the expression and consequent release of inflammatory cytokines, including IL-2 and IFN-γ ( Lemire et al ., 1985 ).…”
Section: Steroid Hormonesmentioning
confidence: 99%